Persistent Symptoms, Lyme Disease, and Prior Trauma. Issue 5 (21st May 2022) - Mustafiz, Fayel; Moeller, James; Kuvaldina, Maria; Bennett, Clair; Fallon, Brian A.
Abstract: One prior study suggests that traumatic events before Lyme disease play an important role in symptom severity. We examined this hypothesis among 60 individuals with persistent symptoms after Lyme disease using validated measures of trauma history, mental and physical symptoms, and functional status. Analysis of variance with Tukey-Kramer multiple comparisons test revealed that a greater number of traumatic events were significantly associated with greater symptom severity on the scales of mood (stress, depression, and anxiety), cognition, multisystem symptom burden, and functional status (mental and physical), but not on measures of pain and fatigue. The effect sizes—meaningful but not large (0.17–0.29)—were mostly produced by comparison with individuals reporting multiple prior traumatic events, representing half of the posttreatment Lyme disease syndrome (PTLDS) group. In conclusion, although PTLDS may be exacerbated by past trauma, trauma plays a role in only a subgroup of PTLDS. Whether addressing prior trauma can improve outcomes in this subgroup requires study.